2003
DOI: 10.1046/j.1442-2050.2003.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental examination of the healing process of telescopic esophageal anastomosis

Abstract: The basis of telescopic anastomosis is old, only the practical details of it have changed and improved. The telescopic anastomosis technique is successfully applied in our practice for reconstruction of gastrectomy and esophageal resection. The reason for this study was that data about the healing process of telescopic anastomosis had not been found in the literature. We used four groups of mongrel dogs for our experiments: Group A (n = 3) received 20 mm-long invaginations with a survival time of 7 days; Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Excessive perfusion pressure can lead to insu cient blood perfusion, inadequate oxygen supply, and an increased risk of postoperative obstruction, dyspnea, and anastomotic rupture (23). The anastomotic blasting pressure wascarried out in animals and in vitro experiments (33)(34)(35). One experimental study showed that the colorectal anastomosis can be ruptured at 70-184 mmHg pressure, which demonstrates that there was a risk of rupture when 400ml liquid was injected (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive perfusion pressure can lead to insu cient blood perfusion, inadequate oxygen supply, and an increased risk of postoperative obstruction, dyspnea, and anastomotic rupture (23). The anastomotic blasting pressure wascarried out in animals and in vitro experiments (33)(34)(35). One experimental study showed that the colorectal anastomosis can be ruptured at 70-184 mmHg pressure, which demonstrates that there was a risk of rupture when 400ml liquid was injected (35).…”
Section: Discussionmentioning
confidence: 99%
“…The anastomotic blasting pressure wascarried out in animals and in vitro experiments (33)(34)(35). One experimental study showed that the colorectal anastomosis can be ruptured at 70-184 mmHg pressure, which demonstrates that there was a risk of rupture when 400ml liquid was injected (35). Anastomotic pressure monitoring is thus recommended for IOLT.…”
Section: Discussionmentioning
confidence: 99%